(untitled) (CIPEEX, 2025)
This study investigates the influence of digital influencers on consumers’ purchase intentions, focusing on the relationship between influencers and companies, as well as the importance of social media presence. A mixed-method approach was employed, combining quantitative data from questionnaires (n=169) distributed to followers of digital influencers in a small Brazilian city, and qualitative insights from workshops with experienced influencers. The results indicate that digital influencers play a significant role in consumers’ purchasing decisions, with a constant presence on social media platforms, particularly Instagram, enhancing consumer trust in promoted brands. The findings highlight the effectiveness of influencer marketing strategies aligned with contemporary consumer behavior, emphasizing the need for strategic collaboration between brands and influencers to maximize impact.